2017
DOI: 10.3390/v9120360
|View full text |Cite
|
Sign up to set email alerts
|

cfa-miR-143 Promotes Apoptosis via the p53 Pathway in Canine Influenza Virus H3N2-Infected Cells

Abstract: MicroRNAs regulate multiple aspects of the host response to viral infection. This study verified that the expression of cfa-miR-143 was upregulated in vivo and in vitro by canine influenza virus (CIV) H3N2 infection. To understand the role of cfa-miR-143 in CIV-infected cells, the target gene of cfa-miR-143 was identified and assessed for correlations with proteins involved in the apoptosis pathway. A dual luciferase reporter assay showed that cfa-miR-143 targets insulin-like growth factor binding protein 5 (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…Concerning the miRNAs studied, as above, a slight prevalence (three studies: Bhattacharyya et al [29] on cystic fibrosis, Podsiad et al [31] on pneumonia, Zhou et al [86] on systemic lupus erythematosus) included miR-155, with the positive results about the use of the respective antagomiR seen in vivo that were confirmed in vitro. miR-143 was successfully tailored in two studies (Tamgue et al [89] on tuberculosis, Zhou et al, [88] on influenza) confirming the positive retrievals already seen in vivo.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Concerning the miRNAs studied, as above, a slight prevalence (three studies: Bhattacharyya et al [29] on cystic fibrosis, Podsiad et al [31] on pneumonia, Zhou et al [86] on systemic lupus erythematosus) included miR-155, with the positive results about the use of the respective antagomiR seen in vivo that were confirmed in vitro. miR-143 was successfully tailored in two studies (Tamgue et al [89] on tuberculosis, Zhou et al, [88] on influenza) confirming the positive retrievals already seen in vivo.…”
Section: Resultsmentioning
confidence: 77%
“…Sixteen studies on animals were found for this macro-category, with the condition more largely studied being influenza (four studies). All but two of these studies were carried out on mice or rats, whereas Asquith et al [85], studied chronic ethanol consumption in non-human primates, and Zhou et al [88] assessed the effect of miRNAs and antagomiRs in influenza in one-month-old beagles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, antiviral proteins produced from human lung epithelial cells and dendritic cells were controlled by several influenza A virus-mediated microRNAs [33,34,35]. In addition to human cells, few studies demonstrated in vivo and in vitro microRNA expression in dogs infected with canine influenza A viruses [36,37]. Nonetheless, canine microRNAs’ response to seasonal human influenza virus infection has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%